A case report of management of intruded mandibular incisors in a young child with epilepsy / Dayang Fadzlina Abang Ibrahim, Siti Hajar Hamzah and Alaa Sabah Hussein - Abang Ibrahim, Dayang Fadzlina; Hamzah, Siti Hajar; Hussein, Alaa Sabah (Faculty of Dentistry, Universiti Teknologi MARA, 2024)
The most common dental trauma during early childhood is intrusive luxation, which results in the displacement of the tooth into its alveolus. It is a severe form of dental trauma that can cause damage to the periodontal ligament, pulp, and alveolar bone. The International Association of Dental Traumatology recommends either extraction or spontaneous re-eruption of the intruded primary tooth, depending on the severity of the intrusion. This case report provides a brief insight into the management of intruded mandibular primary incisors caused by an epileptic attack in a 4-year-old boy diagnosed with refractory spastic cerebral palsy. After 6 weeks of the traumatic incident, spontaneous eruption of the intruded teeth was observed. However, the teeth were found to be mobile after 9 months of clinical and radiographic monitoring, necessitating extraction. Conservative management including waiting for spontaneous eruption with close monitoring is a treatment option for intrusive primary teeth in young children.